2018
DOI: 10.5999/aps.2017.01382
|View full text |Cite
|
Sign up to set email alerts
|

Safety of long-term subcutaneous free flap skin banking after skin-sparing mastectomy

Abstract: BackgroundA persistent problem in autologous breast reconstruction in skin-sparing mastectomies is skin restoration after skin necrosis or secondary oncological resection. As a solution to facilitate reconstruction, skin banking of free-flap skin has been proposed in cases where the overlying skin envelope must be resected, as this technique spares the patient an additional donor site. Herein, we present the largest series to date in which this method was used. We investigated its safety and the possibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…the uppermost layer of the skin is harvested. 30 In this procedure, there is no bleeding from the site where the skin is harvested from and there is no disfigurement to the body also. After the procedure, the team bandage the parts from where the skin is removed in a proper way.…”
Section: Skin Procurementmentioning
confidence: 99%
“…the uppermost layer of the skin is harvested. 30 In this procedure, there is no bleeding from the site where the skin is harvested from and there is no disfigurement to the body also. After the procedure, the team bandage the parts from where the skin is removed in a proper way.…”
Section: Skin Procurementmentioning
confidence: 99%
“…Several studies have reported on salvage methods for cases in which mastectomy flap necrosis develops following immediate breast reconstruction. Verstappen et al 3 attempted in situ skin banking during immediate autologous breast reconstruction after skin-sparing mastectomy, using the former when necrosis developed. If necrosis did not develop, their plan was to remove this under local anesthesia around 7 days after the surgery; infections and other complications were not found to be reported.…”
Section: Sirmentioning
confidence: 99%